2008
DOI: 10.2337/db07-0970
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Replication of a Novel Obesity Locus on Chromosome 1q24 in Isolated Populations of Cilento

Abstract: OBJECTIVE-Obesity is a complex trait with a variety of genetic susceptibility variants. Several loci linked to obesity and/or obesity-related traits have been identified, and relatively few regions have been replicated. Studying isolated populations can be a useful approach to identify rare variants that will not be detected with whole-genome association studies in large populations.RESEARCH DESIGN AND METHODS-Random individuals were sampled from Campora, an isolated village of the Cilento area in South Italy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…The consistent effect observed with both plasma lipid and lipoprotein traits suggests that INSIG2 may play a The genetic variant of INSIG2 that was recently implicated in obesity through a genome-wide association study performed in the Framingham Heart Study 1 has been inconsistently replicated by other research groups. [3][4][5][6][7][8][9][10][11][12][13][14] In the present study, using 32 SNPs, we show that a dense map of the INSIG2 locus, including the previously reported SNP, rs7566605, did not yield a significant association with BMI. The lack of reproducibility of rs7566605 with obesity seen in our study could be due to several reasons, including insufficient power, heterogeneity of ascertainment, and/or unknown gene-gene or gene-environment interactions.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The consistent effect observed with both plasma lipid and lipoprotein traits suggests that INSIG2 may play a The genetic variant of INSIG2 that was recently implicated in obesity through a genome-wide association study performed in the Framingham Heart Study 1 has been inconsistently replicated by other research groups. [3][4][5][6][7][8][9][10][11][12][13][14] In the present study, using 32 SNPs, we show that a dense map of the INSIG2 locus, including the previously reported SNP, rs7566605, did not yield a significant association with BMI. The lack of reproducibility of rs7566605 with obesity seen in our study could be due to several reasons, including insufficient power, heterogeneity of ascertainment, and/or unknown gene-gene or gene-environment interactions.…”
Section: Discussioncontrasting
confidence: 54%
“…2 However, subsequent studies performed by other groups could not replicate the association. [3][4][5][6][7][8][9][10][11][12][13][14] A recent meta-analysis suggested that different study designs might have contributed to these heterogeneous results. 15 …”
mentioning
confidence: 99%
“…In particular, a recent linkage analysis of quantitative traits in the less inbred isolated populations of Cilento was based on this procedure. Interestingly, this led to the detection and replication of a new locus for BMI on chromosome 1q24 [Ciullo et al, 2008]. Other usages, including implementing simulation-based linkage statistics on larger sub-pedigrees, might also be interesting to consider.…”
Section: Discussionmentioning
confidence: 99%
“…PRDX6 is an antioxidant enzyme with calcium-independent phospholipase A2 activity ( 42 ). PRDX6 was identifi ed in a recent study as a possible candidate gene underlying a novel obesity locus on chromosome 1q24 in an isolated population of Cilento, Italy ( 43 ). Recently, a study of 21,000 individuals identifi ed PRDX6 associated with body mass index (BMI) as an indicator of obesity ( 44 ).…”
Section: Canonical Pathway Analysismentioning
confidence: 99%